Mandibular third molar development staging to chronological age and sex in North Indian children and young adults - Rai, B.; Anand, S.C. (The Journal of Forensic Odonto-Stomatology - JFOS, 2023)
Age estimation is not only important for clinical but also for medico-legal purposes. The present study is an attempt to estimate the chronologic age based on the stages of third molar development following the eight stages (A–H) 8 method of Demirjian et al and to compare third- molar development by sex and age. We examined 250 orthopantomograms of young north Indian subjects of known chronologic age (range, 7-26 years). Statistical analysis was performed using the Mann-Whitney U-test and the Wilcoxon test between sex and age. Regression analysis was performed to obtain BR regression formulae for dental age calculation with the chronologic age. Statistically significant differences in mandibular third-molar development between males and females were revealed regarding the calcification stages D and G. The results further indicated that third-molar formation was attained earlier in females than in males. Statistical analysis showed a strong correlation between age and third-molar development for both the sexes.